Bullet train - Isaka, Kōtarō 1971- (Harvill Secker, 2021)
"Satoshi looks like an innocent schoolboy but he is really a viciously cunning psychopath. Kimura's young son is in a coma thanks to him, and Kimura has tracked him onto the bullet train headed from Tokyo to Morioka to exact his revenge. But Kimura soon discovers that they are not the only dangerous passengers onboard.Nanao, the self-proclaimed 'unluckiest assassin in the world', and the deadly partnership of Tangerine and Lemon are also travelling to Morioka. A suitcase full of money leads others to show their hands. Why are they all on the same train, and who will get off alive at the last station?"--Publisher